Feasibility of a Project-Based Electronic Module on Environmental Change to Promote Environmental Awareness and Support SDG 13 - Deden Ibnu Aqil Aqil; Hafid Abbas; I Made Astra; Sisean Baga (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2026)
Objective: To evaluate the feasibility of the Project-Based Learning (PjBL) Environmental Change Electronic Module, known as E-Ling, as an interactive digital teaching material designed to support environmental change learning and improve students’ environmental awareness improve students’ environmental awareness and support SDG 13 (Climate Action). Method: Using a development approach with the ADDIE model, limited to the development stage. The feasibility of the E-Ling module was assessed through expert validation involving 12 experts in material, language, learning, and media. The instrument used was a validation questionnaire, and the data were analyzed using percentage-based feasibility criteria. Results: The expert validation results showed that the developed PjBL-based E-Ling module obtained positive feasibility scores, namely 92.33% from material experts, 80% from language experts, 84.71% from learning experts, and 86.33% from media experts. These results indicate that the module is categorized as good and requires no major revision. Novelty: The development of a PjBL-based electronic module that integrates environmental change materials, learning videos, interactive access through website or application platforms, and project activities to encourage students to learn independently and develop environmental awareness.